PERAN PEMERINTAH KABUPATEN KARO DALAM PENANGGULANGAN BENCANA ALAM ERUPSI GUNUNG SINABUNG KABUPATEN KARO SUMATERA UTARA TAHUN 2013 – 2015 - Febrin, Renny; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was motivated by the concern of Mount Sinabung eruption that has been happened since 2013. Many parties have to synergize and coordinate well to involve in this disaster management by giving services to the refugees that are scattered in several evacuation posts. The purpose of this research is to determine the role of Karo District Government in settling the Mount Sinabung eruption and the factors that obstruct and support the settlement of this disaster. The method used is descriptive and qualitative method which can be defined as the process of solving problems by describing the situations of the subject and object of the research based on the current facts.the theory used in this research include Government Management, Government Coordination and Disaster Management. Based on the result we can conclude the role of each departement are related, among Disaster Management Agency (BPBD) Karo tasked as the overall coordination of the disaster management process, the Office of Social Affairs is responsible for the fulfillment the logistics of refugees, the Public Works Departement is responsible for the evacuation process, fulfill the needs of clean water for bathing, washing, toilet, and handling the post evacuation, the Departement of Health is responsible for guranteeing public health of refugees and provide aid to refugees who are sick. Each relevant department has been manage the refugees of Mount Sinabung eruption as much as possible even though there are still some lacks of coordination. However, there are no obstacles in funding the refugees’ needs to fulfill their decent life.Keywords : Role of Government, Coordination, Disaster Managemen